An Analysis of Agency in Thai Education Policy: A Corpus- Driven Approach - Satienchayakorn, Natakorn; Jimarkon, Pattamawan (rEFLections, 2024)
The most important skill in modern education is critical thinking and its necessary elements are agencies and voices which are force, ability, or power to make decisions or changes. Despite numerous efforts to increase Thai students’ critical thinking skills, their ability to construct social and academic arguments is still far too weak. In addition, while these efforts mainly focus on students’ critical thinking skills, little attention has been given to other education stakeholders such as education, institutions, schools, and teachers which potentially provide room for teachers and students to be critical. In this study, we investigated the ideological indexation of education stakeholders in a series of Thai educational policies (TEPs) years 2016-2018 from the Ministry of Education, Thailand. In TEPs, we utilized the corpus linguistic frequency function to locate the possible stakeholders and applied the framework of syntactic corpus analysis for agency identification (FO-SCAAI) to lexically elicit their agencies and voices which are important elements in modern education. The findings revealed an understanding of the representation of varying degrees of education stakeholders’ agencies in TEPs. The implications of this study will lead to the realization that education stakeholders lack agencies and voices. We hope that upon realizing their lack of agency, the involved parties will make changes by providing more agencies to education stakeholders through modern education in Thai education policies.